Research on surrounding rock-composite arch coupling support models considering pre-tightening force strengthening coefficients - Li, Zhongwei; Li, Xiang (Frontiers in Earth Science, 2025)
BackgroundWith increasing coal mining depth, underground geological conditions grow more complex. Surrounding rock stability control has become a critical bottleneck for safe coal mining. Thus, there is an urgent need to develop more reliable support theories for optimizing engineering support parameters.MethodsBased on the surrounding rock strength enhancement theory, this study constructs a coupling support model integrating pre-tightening force reinforcement and composite arch support principles. Through single-factor variable analysis, we investigate the influence of bolt support parameters on anchorage body strength.ResultsBolt length correlates positively with anchorage body support strength, enabling effective reinforcement through adjusting the thickness of the composite arch. Bolt spacing correlates negatively with support strength. Excessive spacing hinders effective superposition of conical compressive stress zones from individual bolts, impeding continuous composite arch structures formation. Pre-tightening force consistently enhances surrounding rock mechanical properties, steadily increasing anchorage body support strength.ConclusionComparative calculations on actual coal mine roadway bolt support designs verify the effectiveness of this coupling support model.